Smith and Ricardo: Aspects of the Nineteenth-Century Legacy - Hollander, Samuel (American Economic Review, 1977)
The standard of reference from which perspective the early literature is evaluated by Joseph A. Schumpeter in his History of Economic Analysis is the (Walrasian) general-equilibrium approach towards productive organization. Ricardian procedures, according to the Schumpeter historiography, are diametrically opposed to the spirit of general equilibrium-above all to its conception of the returns to factor services as competitively-determined prices. In dealing with the determination of the laws regulating distribution-his fundamental problemRicardo proceeded by arbitrarily reducing the number of variables in his model until he was left with but one variable, namely profits, to be determined as a form of residual the difference between the given value of the marginal product of labor-and-capital and the subsistence wage rate by the one equation of his system.' While it is conceded on this view that Ricardo grasped better than any predecessor the conception of economic theory as a general purpose analytical engine, capable of yielding results no matter what the concrete problem that is fed into it, the specific engine devised by Ricardo constituted nonetheless a detour in the development of economic analysis. For Turgot, Adam Smith (in significant chapters of the Wealth of Nations), J. B. Say, Lauderdale, and Thomas Malthus had already achieved a considerable insight into the correct approach towards productive organization, namely one which encompasses distribution envisaged as the pricing of requisite and scarce